PENGARUH MODEL PEMBELAJARAN RESOURCE BASED LEARNING TERHADAP MINAT DAN HASIL BELAJAR IPS SISWA KELAS VIII SMPN 2 KALIDAWIR TULUNGAGUNG - Iis Halimatus Sa'diyah; Jani Jani (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
This research is motivated by a lack of interest in learning and student learning outcomes at SMPN 2 Kalidawir Tulungagung and prefers activities outside the classroom rather than in the classroom, so it requires special attention from teachers and parents to provide extra education for children to be interested in participating. lessons in school. The purposes of this study are 1) To find out the significant effect of the resource-based learning model on students' learning interest at SMPN 2 Kalidawir Tulungagung 2022/2023. 2) To find out the significant effect of the resource-based learning model on student learning outcomes at SMPN 2 Kalidawir Tulungagung 2022/2023. The approach used in this research is a quantitative approach with Quasi Experimental quantitative research. The population in this study were all students of class VIII SMPN 2 Kalidawir, Tulungagung. The samples of this study were 30 students in class VIII A and class VIII B consisting of 30 students. Data collection techniques using questionnaires and tests. The data analysis technique used is the two-sample T-test (Independent Sample T Test). The results showed that 1) the Learning Model had a significant effect on Social Studies Class VIII Students' Interests at SMPN 2 Kalidawir Tulungagung 2022/2023, as evidenced by the acquisition of tcount -2,667 > ttable 2,002, meanwhile the results obtained Sig. (2-sided) is 0.011. Because the value of Sig. 0.011 < significant level ((= 0.05) then Ho is rejected, and Ha is accepted. 2) The Learning Model has a significant effect on Social Studies Learning Outcomes for Class VIII Students of SMPN 2 Kalidawir Tulungagung 2022/2023, as evidenced by the acquisition of tcount -3.002 > ttable 2.002, Meanwhile, Sig. (2-sided) is 0.004. Because the value of Sig. 0.004 < significant level ((= 0.05) then Ho is rejected, and Ha is accepted.